2020
DOI: 10.1371/journal.pone.0240438
|View full text |Cite
|
Sign up to set email alerts
|

Are goals scored just before halftime worth more? An old soccer wisdom statistically tested

Abstract: There is an old soccer wisdom that a goal scored just before halftime has greater value than other goals. Many dismiss this old wisdom as just another myth waiting to be busted. To test which is right we have analysed the final score difference through linear regression and outcome (win, draw, loss) through logistic regression. We use games from many leagues, control for the halftime score, comparing games in which a goal was scored after 1 minute remained of regulation time with games in which it was scored b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Therefore, the objective of this study was to continue deepening the knowledge of women's football. It has been shown that in men's soccer the parts of the match (first half or second half) modify the behavior of some conducts (Greve, Nesbø, Rudi, & Salikhov, 2020). Knowing what criteria or variables are modulating this behaviour in women's soccer can help optimize not only training, but also performance during competition and subsequent success during it.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the objective of this study was to continue deepening the knowledge of women's football. It has been shown that in men's soccer the parts of the match (first half or second half) modify the behavior of some conducts (Greve, Nesbø, Rudi, & Salikhov, 2020). Knowing what criteria or variables are modulating this behaviour in women's soccer can help optimize not only training, but also performance during competition and subsequent success during it.…”
Section: Introductionmentioning
confidence: 99%